Creatividad y su aporte en la elaboración de artículos con materiales reciclados, en los estudiantes de la Unidad Educativa “Ventanas”, cantón Ventanas, provincia los Ríos - Bravo Sabando, Consuelo Bárbara (2017)
Creativity is one of the essential components for the integral formation of the student; from this the teacher must look for strategies that favor the development of it; In this sense, in the present research work, this variable of study has been linked to recycling; because the accumulation of solid waste has generated a problem inside educational institutions. From there; a study has been created to know to what extent the application of a recycling plan for the elaboration of artisanal products with recycled materials, maintains an incidence in the potentialization of the creativity of the students, which was reflected due to the lack of environmental culture by 80% of the members of the educational community. This was complemented by the ignorance on the part of the methods of certain strategies of recycling and elaboration of handicrafts as techniques for the development of creativity in their students. The results of this research showed that 95% of the educational community is important for the development of creativity. It was also determined that the main cause for accumulation of garbage inside the educational institutions is the lack of a recycling plan and in terms of the development of creativity, it is evident that teachers do not dominate the recycling strategies or the development of creativity based on the reuse of cleaner products